From the concept of giftedness to the construct of high intellectual abilities. Implications for educational policies, normative interpretation and attention to these students - Murciano Rubia, Fátima (Avances en Supervisión Educativa, 2024)
The construct of High Intellectual Abilities includes terms such as giftedness, precocity, genius, talent, and twice-exceptional, encompassing a heterogeneous population with diverse educational needs. Since 1970, legal frameworks in Spain have sought to ensure adequate support for these students. The terms "giftedness" or "superior abilities" were most commonly used, while "high intellectual abilities" first appeared in 2002 in an Order from Extremadura and in 2006 in the Organic Law of Education (LOE). This article examines the implications of specific terms and theoretical models for giftedness in interpreting legal frameworks and implementing educational policies, as well as their impact on the support provided to these students. It also reviews decisions by educational authorities to identify and implement tailored measures. The article contrasts research on high abilities with existing legislation and policies in Spain, analyzing identification data, the role of active associations, intervention programs, and their impact on students’ development. Finally, it highlights the role of educational inspection as a guarantor of the best interests of the child, proposing teacher training guidelines and setting the stage for future analysis in special and post-compulsory education.